The societal costs of chronic pain and its determinants: The case of Austria. - Susanne Mayer; Jonah Spickschen; K Viktoria Stein; Richard Crevenna; Thomas E Dorner; Judit Simon (PLoS ONE, 2019)
Background Chronic pain is among the most burdensome conditions. Its prevalence ranges between 12% and 30% in Europe, with an estimated 21% among Austrian adults. The economic impact of chronic pain from a societal perspective, however, has not been sufficiently researched. This study aims to provide an estimate of the societal costs for working-age adults with chronic pain in Austria. It explores the impact of sex, number of pain sites, self-reported pain severity, health literacy and private health insurance on costs associated with chronic pain. Methods A bottom-up cost-of-illness study was conducted based on data collected from 54 adult patients with chronic pain at three Viennese hospital outpatient departments. Information on healthcare costs including out-of-pocket expenses and productivity losses due to absenteeism and informal care were collected over 12 months. Resource use estimates were combined with unit costs and mean costs per patient were calculated in € for year 2016. Results Mean annual societal costs were estimated at EUR 10191. Direct medical costs were EUR 5725 including EUR 1799 out-of-pocket expenses (mainly pain relieving activities and private therapy). Productivity losses including informal care amounted to EUR 4466. Total costs for women and patients with three or more pain sites were significantly higher. No association with health literacy was found but there was a tendency towards higher out-of-pocket expenses for patients with complementary private health insurance. Conclusion This study is the first to provide a comprehensive assessment of the individual and societal burden of chronic pain in Austria. It highlights that chronic pain is associated with substantial direct medical costs and productivity losses. Patient costs may show systematic differences by health insurance status, implying a need for future research in this area.